Circulating Epstein-Barr virus DNA associated with hepatic impairment and its diagnostic and prognostic role in patients with gastric cancer - He, Hui-Chan; Han, Rui; Xu, Bo-Heng; Huang, Chan; Li, Min-Min; He, Cai-Yun; Lin, Wen-Qian (Frontiers in Medicine, 2022)
Epstein–Barr virus (EBV) infection may affect all tissues and organs of the body. Little is known about the impact of this entity on its systematic incorporation in patients with gastric cancer (GC). This study enrolled a total of 113 GC patients with EBV infection (EBVaGC) and 167 GC patients without EBV infection (EBVnGC). It was found that the CRP levels (indicative of inflammatory status) were significantly increased in EBVaGC compared with those in EBVnGC (12.11 mg/L vs. 5.72 mg/L, P = 0.008), but WBC and neutrophils counts were similar in both groups (P > 0.05). Consistent elevations in the levels of liver enzymes, ALP and GGT, with incompatible alterations in ALT or AST were observed in EBVaGC. Slightly prolonged coagulation indices, PT and INR, and decreased albumin consistently suggested impaired synthesis capability of the liver in EBVaGC (all P < 0.05). The level of circulating EBV DNA was positively correlated with the level of GGT, tumor marker CA72-4 and the lymphocyte infiltration in tumor tissues (all P < 0.05). Of note, the EBV associated high-lymphocyte infiltrated tissues presented rich CD8 + T cells. Circulating EBV DNA further showed a predictive role in distinguishing EBVaGC from EBVnGC (AUC 0.79, 95% CI 0.73 to 0.85, P < 0.001), and was associated closely with better overall survival (HR 0.45, 95% CI 0.21 to 0.96, P = 0.039). EBV infection in patients with gastric cancer may be linked to hepatic impairment and immune response. Circulating cell-free EBV DNA is not only a biomarker for the screening of an EBV-related GC subtype but is also an independently prognosis factor for the long-term survival benefit in GC patients.